Missionary diplomacy: religion and nineteenth-century American foreign relations - Conroy-Krutz, Emily (Cornell University Press, 2024)
"Missionary Diplomacy traces the connections between the Protestant foreign mission movement and the US State Department over the nineteenth century, with particular attention paid to the development of new ideas about citizenship, religious freedom, and humanitarianism."--